HEREDITARY TRANSMISSION OF PATRIMONY AND SOCIAL REPRODUCTION IN A RURAL PARISH OF THE PROVINCE OF MARACAIBO (VENEZUELA) AT THE END OF THE ANCIENT REGIME - Rincón Rubio, Luis (2016)
A study is made of the family system in the rural parish Immaculate Conception of La Cañada, Province of Maracaibo (Venezuela) in the late eighteenth century and early nineteenth century, in the dimension of intergenerational transmission of property rights. This is done by studying the actual inclusiveness or restriction of junior adults in the family group in relation to the transfer of rights and the time of transmission of property rights between the elder and younger generations for a group of families in the parish, through the analysis of hereditary property inventory and partition files. No significant distortions are observed from the prevailing egalitarian inheritance pattern in the parish based on factors such as gender or primogeniture: This confirms previous findings that show the predominance in the parish of an ethics of legitimacy between generations based on the principle of cognatic kinship, where social life is represented as a network of relationships between collateral blood relatives. This paper complements the few existing studies and increases the knowledge on family systems and inheritance practices in Latin America during the Ancient Regime.